2021
DOI: 10.1016/j.chemosphere.2021.129900
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological changes in Oreochromis mossambicus (Peters, 1852) ovaries after a chronic exposure to a mixture of the HIV drug nevirapine and the antibiotics sulfamethoxazole and trimethoprim

Abstract: The burden of the human immunodeficiency virus and acquired immunodeficiency syndrome (HIV/AIDS) infection has transformed the African continent into a major consumer of antiretrovirals (ARVs) drugs. In addition to HIV burden, the African continent has also a high incidence of tuberculosis (TB) and has been experiencing recurring outbreaks of several other viral, bacterial, and parasitic epidemic diseases. The novel severe acute respiratory syndrome coronavirus 2 (SARS-COV-2 or Covid-19) pandemic outbreak is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…Environmental concerns on antibiotics and antivirals; ivermectin and azithromycin had high effects in aquatic organisms. [8,16] Impairment of reproductive system in fish Abnormalities in fish ovaries [17] Disinfectants Strong biocidal properties against bacteria and viruses Formation of dioxin and other carcinogen in surface waters. High ecological risks [18,19] Water as a medium to spread viruses SARS-CoV-2 detected in feces Increase of COVID-19 cases and evidence its presence in waste waters [20][21][22][23] Transmission of virus from wastewater to surface water…”
Section: Reasons Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental concerns on antibiotics and antivirals; ivermectin and azithromycin had high effects in aquatic organisms. [8,16] Impairment of reproductive system in fish Abnormalities in fish ovaries [17] Disinfectants Strong biocidal properties against bacteria and viruses Formation of dioxin and other carcinogen in surface waters. High ecological risks [18,19] Water as a medium to spread viruses SARS-CoV-2 detected in feces Increase of COVID-19 cases and evidence its presence in waste waters [20][21][22][23] Transmission of virus from wastewater to surface water…”
Section: Reasons Referencesmentioning
confidence: 99%
“…The increased use of antiviral and antibiotics also results in increased waste of these medicines in water bodies. Nibamureke and Wagenaar [17] reported that medicinal waste could result in impaired fish reproduction. Tarazona et al [16] developed models to predict the impacts of antibiotics and antiviral drugs on the ecology of aquatic ecosystems and showed sub-lethal effects on fish.…”
Section: Medical Wastesmentioning
confidence: 99%
“…Pharmaceuticals of emerging concern in African surface waters include antiretrovirals and antibiotics [108]. Antibiotics rank as one of the most commonly used and consumed pharmaceutical classes, with low levels widely detected in sewage treatment plants effluent, surface water, groundwater, and drinking water [69].…”
Section: Sulfamethoxazolementioning
confidence: 99%
“…After use, the drugs and their incompletely metabolized parts are excreted via the urine or feces of patients . Due to the low removal of these chemicals by wastewater treatment plants (WWTPs), they are eventually released into aquatic environments via effluent discharge. Consequently, WWTPs are a primary source of antiviral drug discharge, and antiviral drugs have been widely detected in natural water bodies. , In particular, the response to the coronavirus disease-2019 (COVID-19) pandemic has resulted in the considerable release of antiviral drugs into aquatic environments, which is likely to pose a high risk to the aquatic ecological environment. Moreover, chlorine disinfection has been ubiquitously applied as a post-treatment in WWTPs to control microbial pathogens, especially during the pandemic. The presence of active chlorine can react with pharmaceuticals during water chlorination and lead to the formation of transformation products (TPs), which may have hazardous effects on the environment and humans. However, numerous TPs generated from antivirals during water chlorination and their potential environmental risks in aquatic environments are unknown.…”
Section: Introductionmentioning
confidence: 99%